(untitled) (Journal of the College of Basic Education, 2023)
The Palestinian Communist Party is one of the oldest leftist parties in the Arab East, and from it Marxist thought spread in Egypt and the Levant. The Communist Organization was not influential in the Arab circles in Palestine, because its ideas came with the European Jews immigrants. The party played an important and tangible role after its leadership was assumed by Moein Bseiso, who is considered one of the charismatic leadership cadres because of his culture and simple style of addressing the masses because he is one of the prominent Palestinian poets. And through the party’s alliance with the Palestinian national political forces, the party succeeded after the June 1967 war in establishing some political and electoral alliances